Reserve stem cell population in intestinal crypts found to be consistently small by analysis of in vivo clonogenic assays with a biomathematical dynamic model - Bahn, Emanuel; Debus, Jürgen; Alber, Markus (Radiotherapy and oncology, 2018)
Background and purpose - The high plasticity of the intestinal epithelium is maintained by a resilient reserve stem cell population, whose extent and biology are a matter of ongoing debate. The in vivo clonogenic assay (IVCA), presents a well established and efficient analysis of radiation insult to the intestinal crypts. However, we found that inadequate mathematical analysis over the last four decades led to systematic errors and contradictory results in estimates of radio-sensitivity and size of the reserve stem cell pool. - Material and methods - We devised a refinement of the IVCA via development of a biomathematical model that delivers a full statistical dynamic description of epithelial radiation injury and subsequent regeneration. We validated the model against cellular and crypt distribution statistics obtained from IVCA experiments and through systematic re-analysis of experimental data from 27 publications. - Results - A full dynamic description of the evolution of stem cell niche population statistics is obtained. A systematic re-analysis reveals a consistent clonogenic content of the crypt of 31±6 cells. The stem cell reserve manifests to be, contrary to prior predictions, radio-resistant: α=(0.22±0.04) Gy−1. - Conclusion - We established a precision tool for the quantitative analysis of radiation insult to the intestinal crypts, which we employ to show that the reserve stem cell population is small, radio-resistant, and remarkably immutable against a large variety of interventions. The increased resolution of the model allows not only a reduction of the number of animals by about 75%, but also to quantify experimentally the influence of additional agents on damage and on regeneration of the stem cell niche.
Gesehen am 03.03.2020